2006
DOI: 10.1086/505857
|View full text |Cite
|
Sign up to set email alerts
|

FU Orionis: The MIDI VLTI Perspective

Abstract: We present the first mid-infrared interferometric measurements of FU Orionis. We clearly resolve structures that are best explained with an optically thick accretion disk. A simple accretion disk model fits the observed SED and visibilities reasonably well and does not require the presence of any additional structure such as a dusty envelope. The inclination and also the position angle of the disk can be constrained from the multibaseline interferometric observations. Our disk model is in general agreement wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
80
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 43 publications
16
80
1
1
Order By: Relevance
“…While the SIMBAD database lists a spectral type of G3Iavar, Kenyon et al (2000) changed it to G0II. In contrast to Hanner et al (1998), who measured an increasing MIR flux shortward of 10 μm, the spectra of Schegerer et al (2006) and Quanz et al (2006) agree very well with ours, indicating that this object was not variable in the MIR between Dec. 2002 and Jan. 2006 (or at least that any period of variability was not observed). No Kurucz model was plotted in the SED of FU Ori as explained in Sect.…”
Section: Appendix A: Comments On Individual Sourcessupporting
confidence: 86%
“…While the SIMBAD database lists a spectral type of G3Iavar, Kenyon et al (2000) changed it to G0II. In contrast to Hanner et al (1998), who measured an increasing MIR flux shortward of 10 μm, the spectra of Schegerer et al (2006) and Quanz et al (2006) agree very well with ours, indicating that this object was not variable in the MIR between Dec. 2002 and Jan. 2006 (or at least that any period of variability was not observed). No Kurucz model was plotted in the SED of FU Ori as explained in Sect.…”
Section: Appendix A: Comments On Individual Sourcessupporting
confidence: 86%
“…This configuration and derived accretion rates were recently confirmed by modeling the infrared spectra of FU Ori stars taken with the Spitzer Space Telescope (Green et al 2006). However, Quanz et al (2006) modeled their mid-IR visibilities of FU Ori without any additional structure such as a dusty envelope and concluded that the presence of an accretion disk is sufficient to explain this object.…”
Section: Fu Ori Accretion Disksmentioning
confidence: 99%
“…The errors of the MIDI spectra are difficult to estimate properly from the present data sets, because the number of standard stars observed close in time to V Oph and at similar airmasses is quite limited (3, 2, and 3 standard stars at epoch 1, 2, and 3, respectively). However, we estimate the errors of the absolutely calibrated spectra to be 10-20%, based on other studies which derived N-band spectra from MIDI data (e.g., Kervella et al 2006;Poncelet et al 2006;Quanz et al 2006). The data set number of each visibility point as given in Table 1 is indicated.…”
Section: Midi Observationsmentioning
confidence: 99%